The influence of dating apps on sexual behavior among female students: a sociocultural analysis - Efendi, Zakaria; Hanim, Meysella Al Firdha; Abdullah, Irwan; Jubba, Hasse; Nurazizah, Siti (Masyarakat, Kebudayaan dan Politik, 2025)
Online dating apps have become a means for some female college students in Yogyakarta to find sexual partners. Apps such as Tinder, Bumble, and Tantan indicate people nearby and have anonymity features that make it easier for users to connect with people, allowing for a freer exploration of sexual identity, thus contributing to the formation of promiscuous sexual behavior among female college students. This study aims to analyze the role of dating apps in shaping promiscuous sexual behavior among female college students in Yogyakarta from a sociocultural perspective. Using a qualitative approach and ethnographic method, this study found that dating apps are used as a means of finding partners to fulfill sexual desires without serious commitment. Factors such as ease of access, anonymity, the flexible social environment, and the influence of popular culture play an important role in reducing the social supervision that previously restricted sexual behavior. The findings suggest that dating apps not only facilitate physical encounters but also create new spaces for female college students to adopt more permissive sexual values. The features of anonymity and ease of access create an open space for the free exploration of sexual identity and the adoption of new values related to sexuality, influenced by popular culture and a flexible social environment.